Pengaruh Pemberian Fosfat Alam dan Bahan Organik pada Tanah Sulfat Masam Potensial Terhadap P-Tersedia Tanah dan Produksi Padi (Oryza sativa L.) - M. Alfaddli Purba; Fauzi Fauzi; Kemala Sari (Jurnal Agroekoteknologi, 2015)
This research was conducted to study the effect of phosphate fertilizer and organic matter in a potential acid sulphate to P-soil available and production of rica (Oryza sativa L.) at Karang Anyar Village, Secanggang Districk. This  research was designed by factorial randomized design with 2 factor and 3 replication . Sample soils were taken with 3 replice randomly at 0-20 cm depth. The first factor is dose phosphate fertilizer are control (P0), 0.64 g (P1), 1.28 g (P2), 1.92 g (P3) and dose of organic matter are control (P0), blotong 40 g (B1), manure 40 g (P2), blotong and manure mixed (P3). The results of this study showed that of natural phosphate in acid sulphate soils can increase the P-available soil at a dose of 1.28 g / 8 kg dose equivalent 1 ton/ha , the highest weight of 1000 grains at a dose of 1.92 g / 8 kg dose equivalent 1.5 ton/ha and the lowest percentage of grain at a dose of 1.92 g / 8 kg . Giving filter cake showed the highest P-available soil. Organic matter showed the highest 1000 grain weight in a mixture of filter cake and manure at a dose of 10 tons / ha. The percentage of low grain in manure 10 tons / ha. Interaction between phosphate at a dose of 1.28 g / 8 kg dose  equivalent 1 ton/ha with a mixture of manure and filter cake, showed the highest P-available soil. Interaction between phosphate at a dose of 1.92 g / 8 kg dose equivalent 1.5 ton/ha with a mixture of filter cake and manure showed the lowest percentage of empty grains. Keywords : Phosphate fertilizer, Organic matter, Interaction, P-available and Production.